Hyperthyroidism in Down’s Syndrome – A Rare Association - Shrestha, Manju; Agrawal, Jyoti; Rai, Basant; Chaudhary, Shipra (Journal of Nepal Paediatric Society, 2022)
Trisomy 21 is the most common chromosomal abnormality in paediatric population, and the most common cause of intellectual disability. The most common endocrine disease in these population is hypothyroidism. Hyperthyroidism is rare in patients with Down syndrome, but is likely to be underestimated. Hyperthyroidism treatment strategy is highly important for an undisturbed and balanced development of the children.The objective of this case report is to highlight the importance of hyperthyroidism in Down syndrome which is the rare presentation, to best of our knowledge.